An odyssey through salpingitis isthmica nodosa. (January 2015) - Bolaji, Ibrahim I.; Oktaba, Monika; Mohee, Kevin; Sze, Ka Yan Shirley
Abstract: Salpingitis isthmica nodosa (SIN) is a nodular swelling of the isthmic segment of the fallopian tube. It is of unknown aetiology and is usually an acquired pathologic condition resulting from direct invasion of the muscularis layer by the endosalpinx in the isthmic portion of the fallopian tube between the lumen and the serosa. The clinical significance of SIN rests on its strong association with tubal ectopic pregnancy and subfertility. Assisted reproductive technology (ART) has improved the reproductive capability of SIN patients. Unlike ART, which bypasses pelvic pathologies, tubal surgical approaches improve fertility by correcting the pathology and can improve a patient's related symptoms of pelvic pain and abnormal menstruation, and provide a permanent cure. This paper gives an update on the epidemiology, aetiology, diagnosis and management of SIN and concludes that despite the reported successes with tubal surgery, the mainstay of treatment remains ART in (in the UK) centres recognised by the Human Fertilization and Embryology Authority (HFEA). The success of surgical infertility therapy depends on careful selection of cases using appropriate investigative techniques, with the procedures carried out in centres with sufficient expertise.